An examination of the role of domestic destinations in satisfying holiday demands. (February 2016) - Davison, Lisa; Ryley, Tim
Abstract: The role of domestic destinations in satisfying demand for holidays has received less attention than research which outlines the challenges associated with long haul travel, particularly within the United Kingdom context. This paper examines the role of domestic holidays in satisfying demand in relation to international holidays, in the context of providing a better understanding of the environmental impacts of tourism. This is achieved through analysis of a household survey and a series of interviews with family groups of holiday-makers. The data was collected in the East Midlands region of the United Kingdom. Most respondents prefer domestic holidays in attractive coastal and rural destinations; they often take place in the summer and for shorter periods than overseas trips. Yet once at the destination there is commonality between tourism practices in domestic and international destinations. Socio-cultural aspects, life stage and financial considerations prove much more influential than environmental concerns in influencing choice. In response, the main policy recommendation would be to raise the relative cost of travelling abroad. The primary research recommendation would be to deepen the understanding of how substitution between destinations can occur. Highlights: Attractive coastal and rural UK destinations during summer months predominate. There is commonality in tourism practices in domestic and international destinations. Socio-cultural aspects, life stage and financial considerations are most influential. The main policy recommendation is to raise the relative cost of travelling abroad. Research deepening the understanding of substitution between destinations is needed.